2016
DOI: 10.3892/mmr.2016.5174
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically increased ILC2 and Th9 cells in lung tissue jointly promote the pathological process of asthma in mice

Abstract: In recent years, T helper (Th) 9 cells have been demonstrated to be key mediators in immune responses in asthmatic lungs, and innate lymphoid cells 2 (ILC2s) have been described as a novel type of innate immunocyte with the ability to enhance immunoglobulin E (IgE) production. However, the interaction between ILC2s and Th9 cells in the pulmonary system of a mouse model of asthma remains to be elucidated. In the present study, the response state of lung tissue with regards to Th9 and ILC2s in a mouse model of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Lung ILC2s are known to play an important role in the development of allergic inflammation, and ILC2 numbers are elevated in the peripheral blood and sputum of asthma patients (Smith et al, 2016; Ying et al, 2016). ILC2s are involved in other lung diseases, including chronic obstructive pulmonary disease (Silver et al, 2016), fibrosis (Hams et al, 2014), and tumors (Trabanelli et al, 2017; Chevalier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lung ILC2s are known to play an important role in the development of allergic inflammation, and ILC2 numbers are elevated in the peripheral blood and sputum of asthma patients (Smith et al, 2016; Ying et al, 2016). ILC2s are involved in other lung diseases, including chronic obstructive pulmonary disease (Silver et al, 2016), fibrosis (Hams et al, 2014), and tumors (Trabanelli et al, 2017; Chevalier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ILC2-derived IL-5 is critically involved in increased IgM production (Drake et al, 2016 ). Polarized ILC2s and Th9 cells also stimulate each other in mouse models of asthma in the lung (Ying et al, 2016 ).…”
Section: Ilc2s In the Lungmentioning
confidence: 99%
“…ILC2s are dependent on GATA3 and retinoic acid receptor‐related orphan receptor‐ α (ROR α ) for their development and function. Several researches have demonstrated that the ILC2s promote and induce the development of CD4 + Th2 cell‐dependent immunity . Thus, we proposed a hypothesis that there may be ILC2s in peripheral blood which related to Th2‐associated inflammation.…”
Section: Introductionmentioning
confidence: 91%